محددات توجه الشباب الجامعي نحو النشاط المقاولاتي -دراسة میدانیة على عینة من الشباب الجامعي - هاملي عبد القادر (Finance and Business Economies Review, 2018)
The purpose of this paper is to highlight the reality of entrepreneurial spirit among Algerian youth and to determine the role that played by Determinants of entrepreneurship in order to create this desire among Algerian youth. The data were collected through a questionnaire, which was distributed, to about 250 students from two institutions selected from the Algerian west, only 164 were retrieved and used for analysis. In order to answer this problem. We have used the Confirmatory Factor Analysis (CFA) to purify the model and to determine the main dimensions of Determinants of entrepreneurship. Where the modeling of structural equations was used through the Partial Least Squares - Path Modeling method (PLS-PM), so as to test hypotheses and to define the relationship between Determinants of entrepreneurship and entrepreneurial spirit among Algerian youth The findings of the study revealed there is no positive effect of these Determinants on the creation of the entrepreneurial spirit in the target sample. And it recommended the need to pay more attention to this philosophy by, Developing the work, and programs of the support, and accompaniment apparatus, Enhance the social environment, and give it a pivotal role, in creating a culture of entrepreneurship among young people, both educated and others, The abolition of interest rates, which are one of the most important obstacles, that alienate Algerian youth from the field of entrepreneurship such as those in some developed countries or even some Arab and African countries